Saturation vapour pressure measurements of refrigerant R1224yd(Z) from 274 K to 338 K. (January 2023) - Beltramino, G.; Rosso, L.; Cuccaro, R.; Fernicola, V.
Highlights: Vapour pressure measurements of a new-generation refrigerant (HCFO-1224yd(Z)) were carried out. A high measurement accuracy was achieved (maximum expanded uncertainty of ≈10 hPa). A comparison against the literature data and vapour pressure correlations was performed. Abstract: A new generation of refrigerant fluids, such as hydrofluorolefines (HFOs) and hydrochlorofluorolefines (HCFOs), has been recently introduced in order to increase the availability of zero-ODP (Ozone Depletion Potential) and low-GWP (Global Warming Potential) refrigerants. Among the HCFOs, the refrigerant HCFO-1224yd(Z) captured more attention due to its very low GWP (<1), negligible ODP (0.00023), non-flammability, low toxicity, and good chemical and thermal suitability. Due to its novelty, there is still a lack of thermodynamic property data about this refrigerant including, e.g. the saturation vapour pressure measurements that have been performed only in few experimental works, one of them used to develop the first equation of state in 2017. At INRIM, saturation vapour pressure measurements of the HCFO-1224yd(Z) were carried out in the temperature range from 274 K to 338 K, improving the measurement accuracy of previously available works. The experimental approach was based on a static method where the set-up consisted of a sample cell immersed into a temperature-controlled calibration bath with millikelvin stability, connected to a precision capacitance manometer with a measurement full scale of 0.5 MPa operating at a constant temperature of 373 K. The experimental work and the measurement results are reported together with a comprehensive uncertainty budget and a comparison against measurement data available from previous works.